Tutela jurisdicional coletiva da ordem urbanística - Carvas, Felipe (2014)
The urban order was expressly included as object of collective action in 2001, and with this, it is pertinent to investigate what is the scope and content of his tutelage in court. So first was analyzed the term "urban order" in order to identify its component institutes and other features that are particularly important for their protection, considering principally the provisions of the federal law called City Statute . Subsequently, we analyze the Brazilian class action, which general discipline occurs with the interaction between the Code of Consumer Protection and the Law of Public Civil Action. We also analyze other actions related to collective protection, such as the popular action, the collective writ of mandamus and collective action of adverse possession